Advertising as a Creative Industry Regime of Paradoxes - Derda, Izabela (Routledge Research in the Creative and Cultural Industries, 2024)
At the crossroads of culture and commerce, the advertising industry is a regime of paradoxes. This book examines the place of advertising on today's creative industries, exploring the major challenges advertisers confront as they engage with other creative sectors. Izabela Derda, author, media scholar, and industry expert, offers insights into how the industry keeps deconstructing its own creative processes and collaborative models as it attempts to stay relevant. Through extensive case studies and interviews with industry professionals and thought leaders, this book examines the sector's struggle to adapt to new business models and to monetize creativity in today's media landscape, from re-engaging audiences through media more typical of arts and entertainment to managing intricate cross-sectoral creative collaborations. From redesigning workplaces to satisfy the expectations of the youngest generations of creatives to reconsidering the paradigm of conventional creative teams, the advertising sector has swiftly adjusted to the seismic changes in today's media landscape. The book will be of interest to scholars and students of creative media, advertising, and media studies, as well as those interested in understanding the changing complexities and latest innovations of the creative industries. Advertising professionals, artists, and policymakers will find relevant insights and possible solutions for the major challenges facing the advertising industry today.